Optimized Purification of CIDRα-PfEMP1 Plasmodium falciparum Recombinant Protein with Affinity Chromatography - Alami, Eqiel Navadz Akthar; Sulistyaningsih, Erma; Kusuma, Irawan Fajar; Rachmania, Sheilla (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
Interaction of Cysteine-rich Interdomain Region (CIDR)α-Plasmodium falciparum Erythrocyte Membrane Protein (PfEMP1) and Endothelial Cell Receptors especially CD36 on host cells is main malaria pathogenesis, makes this domain as a malaria vaccine candidate. Recently, the development of the malaria vaccine is conducted by recombinant technology, and the purification of the CIDRα-PfEMP1 recombinant protein is a pivotal step. This study aimed to determine an optimal condition to purify the CIDRα-PfEMP1 recombinant protein by affinity chromatography through imidazole and NaCl concentration. The purified recombinant protein was visualized using SDS-PAGE and its concentration was measured using Image J software and Bradford Assay. The data were analyzed using SPSS 26 software, and the Paired T-Test analysis was conducted to compare the concentration of purified recombinant protein from two different methods. The result showed that thetarget band of purified recombinant protein was 27 kDa. The thickest target protein band was observed in purified recombinant protein using 140 mM imidazole and 300 mM NaCl. The recombinant protein concentration using Image J software was 0.025 µg/µL, while the Bradford Assay was 0.56 µg/µL. The Paired T-Test analysis has a significance value of 0.010 (p<0.05), meaning there was a significant difference between the concentration measurement using Image J software and Bradford Assay. In conclusion, the optimized condition to purify the CIDRα-PfEMP1 recombinant protein by affinity chromatography was using 140 mM imidazole and 300 mM NaCl. It is suggested to measure the purified CIDRα-PfEMP1 recombinant protein concentration using the Bradford Assay method due to its convenience and sensitivity.